2002
DOI: 10.1063/1.1477622
|View full text |Cite
|
Sign up to set email alerts
|

Electron field emission from boron-nitride nanofilms

Abstract: Electron field emission from boron nitride nanofilm and its application to graphite nanofiber

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 18 publications
(17 reference statements)
4
57
2
Order By: Relevance
“…It has recently been found that boron nitride coated graphite nanofibers also emit electrons at much reduced (from 1.5 to 0.8 V/mm) the threshold with high (10 2 level) intensity compared with the uncoated carbon fibers [490]. It is explained that introduction of the BN nanofilm leads to a significant reduction in the effective potential barrier height [491]. A tendency of N-buckling outward the BN nanotubes has been observed theoretically [492].…”
Section: Joint Size and Catalytic Effects: Pl Of Nanometric Siomentioning
confidence: 96%
“…It has recently been found that boron nitride coated graphite nanofibers also emit electrons at much reduced (from 1.5 to 0.8 V/mm) the threshold with high (10 2 level) intensity compared with the uncoated carbon fibers [490]. It is explained that introduction of the BN nanofilm leads to a significant reduction in the effective potential barrier height [491]. A tendency of N-buckling outward the BN nanotubes has been observed theoretically [492].…”
Section: Joint Size and Catalytic Effects: Pl Of Nanometric Siomentioning
confidence: 96%
“…In fact, high turn-on fields of 8.3 to 15.2 V lm -1 [202] were measured on microcrystalline BN thin films. For comparison, the best field emitters made of aligned CNTs typically exhibit turn-on fields in the range of 1-3 V lm -1 .…”
Section: Field-emitting Devicesmentioning
confidence: 99%
“…Some reports have presented the field emission characteristics for the BCN [5,6]. The turn-on electric field of the electron emission as low as that of the BN film has been achieved for the BCN film with C composition ratio lower than 20% [7].…”
Section: Introductionmentioning
confidence: 95%